PTU-258 A UK national comparative audit of appropriateness of red cell transfusion in medical patients. (28th May 2012) - Coda, S; Pendry, K; Davies, T; Grant-Casey, J; Wallis, J; Taylor, C; Astbury, B; Hughes, E; Reid, J; Horan, M; Davies, T; Thillainayagam, A V
Abstract : Introduction: The decrease in red cell usage (15%) that has been achieved in recent years has mainly been achieved through the use of blood conservation strategies adopted for surgical patients. Despite national guidelines for blood transfusion being available, agreed triggers for transfusion still need to be established in clinical practice, together with better decision-making in anaemia management to further reduce inappropriate transfusion of red cells in medical patients. Methods: The main aim of this audit was to observe the extent of inappropriate red cell transfusions, taking account of relevant clinical information and pretransfusion assessment. In autumn 2011, a total of 8759 red cell transfusions in medical units from almost all UK hospitals (>90%) were audited in 3 selected weeks. Through an algorithm based on clinical and diagnostic information provided, a panel of expert physicians estimated the appropriateness of the transfusion. Subgroup analysis was also undertaken to identify patients with a reversible cause of anaemia in whom timely diagnosis and treatment of the original condition would have almost certainly prevented the recourse to blood transfusion. Results: Preliminary analysis has revealed many cases of red cell transfusion when the pretreatment haemoglobin (Hb) was within acceptable limits. The findings show that 4.1% cases had a pretransfusion Hb higher than 10 g/dl (median 7.8, range 2.3–17.7) and 5.8% had a posttransfusion Hb of greater than 12 g/dl (median 9.9, range 4.2–19.3). Serum ferritin was measured in only 38% of cases and of these 9.3% of patients had a ferritin <15 μg/l. Of all the transfusion episodes, only 1748 were for blood loss, while 180 were for prophylaxis prior to a procedure. The vast majority were for anaemia, with the remaining 48 reports not having enough data. In blood loss, the commonest indication was haematemesis (1029 cases), while 423 were primarily for rectal bleeding. Conclusion: This national comparative audit shows: (i) there is substantial inappropriate red cell transfusion in medical patients; (ii) gastrointestinal bleeding is far and away the major reason for transfusion in the setting of blood loss among medical patients. The frequent use of red cell transfusion in the absence of clinical necessity seems to derive from the use of above-threshold triggers, and suboptimal management of anaemia with a reversible cause. Competing interests: None declared.